Optimization of BRIN’s Technology License: Conjoint Experimental Study - Supomo, Anggun Dwi Puspo; Balqiah, Tengku Ezni (The Asian Journal of Technology Management (AJTM), 2025)
Abstract. Commercialization of research products is a common problem in the product development stage of research institutions where many research products are not utilized to become commercial value. This study aims to analyze the opportunity evaluation by business actors in utilizing technology products from research institutions, especially the National Research and Innovation Agency (BRIN). Conjoint analysis design was carried out to see respondents' assessments of a series of profiles containing theory-based variable manipulations and their influence on decision making according to opportunity evaluation theory. The questionnaire was filled out by 101 individuals who have decision-making authority in the company and analyzed using the Mixed-effect model regression technique. Opportunity attributes (prototype maturity, segment clarity and regulatory hurdless) have a significant effect on the opportunity evaluation to license BRIN’s research products. We document the moderating role of individual attributes and environmental dynamism attributes on the influence of opportunity attributes on the opportunity evaluation to license BRIN’s research products. This study uses a different approach in analyzing the factors of industry licensing decisions for research products from research institutions by applying opportunity evaluation. This study offers insights for research institutions in utilizing research products for business actors through licensing schemes. Keywords: Commercialization, opportunity evaluation, conjoint analysis, organizational behavior, licensing